Exploring the Shari'ah economic learning model through virtual learning: Initiatives and challenges - Nursaid, Nursaid; Haanurat, A. Ifayani; Rahman, Anisur; Bakhri, Saiful (Assyfa Journal of Islamic Studies, 2024)
The success of Sharia economics is contingent upon adhering to the principles of Islamic economics in all its actions. Because of this, it is essential to get a complete understanding through Sharia economic education, which covers many vital principles that greatly help the growth of national character education with an Islamic focus. Nevertheless, empirical evidence indicates that students must still strive to enhance their capacity to articulate and comprehend real-world phenomena and analyse solutions to societal issues through the lens of Sharia economics. The objective of this study is to develop a comprehensive Sharia economic learning model for students in the Department of Economic Education at the Muhammadiyah University of Jember. The model will enable students to accurately describe and analyse real-life phenomena and provide interpretations and solutions based on the principles of Sharia economics. The study methodology employed is a descriptive approach aimed at elucidating the research findings derived from the respondents and field observations, utilising both primary and secondary data sources. The research will extensively explore the findings related to comprehending Sharia economic material through a direct learning methodology. The article will also highlight the necessary efforts required to optimise the research's objectives.